PENGARUH UMUR, TINGKAT PENDIDIKAN DAN LAMA BERTANI TERHADAP PENGETAHUAN PETANI TENTANG MANFAAT DAN CARA PENGGUNAAN KARTU TANI DI KECAMATAN PARAKAN, KABUPATEN TEMANGGUNG - Gusti, Irganov Maghfiroh; Gayatri, Siwi; Prasetyo, Agus Subhan (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
This research aimed to analyze the affect of farmer ages, levels of education and farming experience toward the level of farmer knowledge about benefit and application method of Kartu Tani in Parakan District, Temanggung Regency. Population of this study were farmers who joined Farmer Group and had a Kartu Tani. Respondent of this study were 60 farmers from two villages. Location of this study were in Dangkel Village and Glapansari Village, Parakan District, Temanggung Regency. Research carried out in July 2021. The research method was survey. Method of collected data this study were with interview, observe, documentary and literature. Interview was based on questionnaire using likert scale. Method of analyze data was using quantitave descriptive analyze. The result of this research that farmer ages, level of education and farming experience significantly affected to the level of farmer knowledge about Kartu tani beneficial and method of use. Partially ages, level of education and farming experience had positive and significant affect to the level of farmer knowledge about Kartu tani beneficial and method of use (abstrak Bahasa Indonesia dan Bahasa inggris tidak sama, mohon disesuaikan).